2014
DOI: 10.2334/josnusd.56.29
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Portland cement combined with different radiopacifying agents

Abstract: The aim of this study was to evaluate the response of rat subcutaneous tissue to Portland cement combined with two different radiopacifying agents, iodoform (CHI 3 ) and zirconium oxide (ZrO 2 ). These materials were placed in polyethylene tubes and implanted into the dorsal connective tissue of Wistar rats for 7 and 15 days. The specimens were then stained with hematoxylin and eosin, and inflammatory reaction parameters were evaluated by light microscopy. The intensity of the inflammatory response to the seal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Cement matrix flaws may exacerbate existing cracks, leading to material degradation (Coomaraswamy et al, 2007). In view of that, PC association with different radiopacifying agents has been proposed to find an alternative to bismuth oxide (de Morais et al, 2006;Bortoluzzi et al, 2009;Húngaro-Duarte et al, 2009;Camilleri et al, 2011;Guerreiro-Tanomaru et al, 2012;Antonijevic et al, 2014;Lourenço-Neto et al, 2014). Iodoform seems to be harmless to connective tissue and it is widely available to clinicians (de Morais et al, 2006;Bortoluzzi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cement matrix flaws may exacerbate existing cracks, leading to material degradation (Coomaraswamy et al, 2007). In view of that, PC association with different radiopacifying agents has been proposed to find an alternative to bismuth oxide (de Morais et al, 2006;Bortoluzzi et al, 2009;Húngaro-Duarte et al, 2009;Camilleri et al, 2011;Guerreiro-Tanomaru et al, 2012;Antonijevic et al, 2014;Lourenço-Neto et al, 2014). Iodoform seems to be harmless to connective tissue and it is widely available to clinicians (de Morais et al, 2006;Bortoluzzi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Iodoform seems to be harmless to connective tissue and it is widely available to clinicians (de Morais et al, 2006;Bortoluzzi et al, 2009). Another tested radiopacifier, zirconium oxide does not affect tissue integrity (Lourenço-Neto et al, 2014;Silva et al, 2014), and furthermore, preserves PC properties (Bortoluzzi et al, 2009;Húngaro-Duarte et al, 2009;Camilleri et al, 2011;Cutajar et al, 2011;Guerreiro-Tanomaru et al, 2012;Weckwerth et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the excellent biocompatibility of MTA is attributed to its alkaline pH and the potential to release calcium ions. Alkaline pH is important for hard tissue induction and antimicrobial activity considering that resistant endodontic bacteria, such as Enterococcus faecalis , are destroyed at a pH values over 11 (17). The results of our study showed that amalgamator and ultrasonic mixing techniques resulted in an increase in solubility and PH.…”
Section: Discussionmentioning
confidence: 99%